The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21678/jb.2018.875
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Advantages as a Complete Mediator Variable in Strategic Resources, Dynamic Capabilities and Performance Relations in the Car Sales Sector

Abstract: Taking the resource-based view-RBV-and the dynamic capability view-DCV-as an orientation, the main aim of this study is to develop the mediator role that competitive advantages play in the relations between strategic resources, dynamic capabilities and performance. The study takes place in a dynamic and changing sector: the sale of new cars in Portugal. The results show that (a) achieving competitive advantages, which are decisive for business results, depends on the available strategic resources and the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Similarly, Pisano [84] found that, under a changing environment, dynamic capabilities were required to choose the right resources to create competitive advantages leading to good organisational performance. In the same vein, Navarro-García and Moreno [50], Breznik and Lahovnik [85] determined that dynamic capabilities influenced organisational performance by passing on competitive advantages. An organisation with dynamic capabilities has the potential to maintain its competitive advantages, leading to future success.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, Pisano [84] found that, under a changing environment, dynamic capabilities were required to choose the right resources to create competitive advantages leading to good organisational performance. In the same vein, Navarro-García and Moreno [50], Breznik and Lahovnik [85] determined that dynamic capabilities influenced organisational performance by passing on competitive advantages. An organisation with dynamic capabilities has the potential to maintain its competitive advantages, leading to future success.…”
Section: Discussionmentioning
confidence: 96%
“…The research found that competitive advantage has a significant influence on the organizational performance. Navarro-García and Moreno [50] studied the relationship between dynamic capacity and organizational performance with competitive advantage as a transmission factor in the car sales business. The results of the research showed that dynamic capacity influenced the organization's performance through a variable of competitive advantage.…”
Section: Competitive Advantagesmentioning
confidence: 99%
“…Within firm resilience literature, there is growing attention to the concept of slack resources, which are the bundle of assets a firm has more than that which is required to sustain day to day operations (Gao et al, 2017;Karacay, 2017;Kiss et al, 2018;Navarro García et al, 2018;Vanacker et al, 2017). Some scholars have given such slack resources salience as they are seen to cushion firms against environmental shocks (Karacay, 2017;Omar et al, 2020).…”
Section: Review Of Theoretical Literaturementioning
confidence: 99%
“…Competitive advantage is utilized to describe a business's relative performance compared to competitors in a certain market environment (Navarro-García et al, 2018). This advantage originates from the absence of certain resources and characteristics by competing businesses in a similar sector that allow some of them to be more competitive than competitors.…”
Section: The Effect Of Competitive Advantage On Business Performancementioning
confidence: 99%